Spatiotemporal characterization of ghrelin and cholecystokinin levels in the gastrointestinal tract of juvenile Sparus aurata: effects of feeding status and diet composition - Caderno, Anyell; Tang, Patrik; de las Heras, Verónica; Gharbi, Naouel; Alarcón-López, Francisco Javier; Mancera, Juan Miguel; Martos-Sitcha, Juan Antonio; Gilannejad, Neda (Frontiers in Endocrinology, 2026)
Appetite regulation in fish relies on complex neuroendocrine pathways within the brain-gut axis, with ghrelin (Ghrl) and cholecystokinin (Cck) as central players. However, their spatial distribution along the gastrointestinal tract (GIT) and responses to feeding status remain poorly understood in teleosts. This study investigated: i) the baseline distribution of Ghrl and Cck levels along the GIT of juvenile Sparus aurata fed a commercial diet; ii) their temporal dynamics during short-term fasting and refeeding; and iii) the influence of diet composition on their spatiotemporal profiles. Juveniles were fed for 92 days with: i) a control diet containing 20% fishmeal (CT); ii) a plant protein diet replacing 60% of fishmeal with hydrolyzed plant protein (PP); and iii) the PP diet supplemented with 2% LB-GreenGrape functional additive (GG). Fish were sampled at 2, 6, and 24 h post-feeding (Cf), after 7 days of fasting (Ft), and at 2, 6, and 24 h post-refeeding (Rf). Hormone levels were quantified across five GIT segments, including the stomach (S1) and four equal intestinal segments (S2–S5). Baseline characterization revealed elevated Ghrl content in S3 and S5, whereas Cck levels were highest in S5. During fasting, Ghrl levels declined, while Cck increased in S1, S2, and S5 with distinct temporal patterns. After refeeding, gastric Ghrl levels (S1) decreased within 24 h, potentially reflecting secretion into plasma and involvement in hunger signaling, although plasma levels were not measured. In contrast, Cck levels in the anterior intestine (S2) rose sharply 24 h after refeeding, suggesting an anticipatory response to refeeding, possibly related to a dual role involving both rapid satiety signaling and preparatory modulation of digestive activity. The PP and GG diets maintained high gastric Ghrl (S1) and lowered intestinal Cck (S2) levels after feeding, especially in the PP diet. This pattern may either prolong satiety and reduce feed intake or reflect changes in hormone release due to lower caloric intake, with the PP diet lowering growth and feed efficiency, partially offset by the functional additive. The study maps Ghrl and Cck in the S. aurata GIT, showing spatial, temporal, and dietary regulation, with implications for aquaculture nutrition.